Glocalised constitution-making in the twenty-first century: Evidence from Asia. Issue 2 (13th June 2019) - DE VISSER, MAARTJE; SON BUI, NGOC
Abstract: How have Asian nations conducted, or how are they conducting, constitution-making in the face of pressures associated with globalisation, and how do they balance those forces with domestic interests and realities? This article aims to develop an analytical framework that can capture this global–local interplay. It introduces the concept of 'glocalised constitution-making' to denote the co-existence and relationship between the two governance levels as manifested in the forces, actors and norms pertaining to the process of drafting a new constitution as well as its substance. Glocalisation permeates the entirety of a constitution-making episode, from the impetus to initiate the process, to its design and inclusiveness of interests featured, and the scope of topics considered. The effects of glocalised constitution-making for domestic drafters are arranged along a continuum with approbation and aversion as the polar opposites. The precise location on the continuum will depend on the value preferences of the domestic stakeholders and the matters under consideration. The application of this analytical framework is illustrated with reference to recent constitution-making exercises in Bhutan, Nepal, Thailand, East Timor and Sri Lanka.